(untitled) (Tempo e Argumento, 2021)
Objective: to analyze the efficacy of the tutela action for the right to mental health in Colombian jurisprudence, 2000-2019. Methodology: qualitative study of hermeneutic approach, through descriptive - retrospective analysis of 85 judgments reviewed and ruled in second instance by the Constitutional Court of Colombia. Conclusions: it is evident that the tendency has been to grant the requested protection and that the plaintiffs are part of the population with more vulnerability. Is remarkable the reiteration of jurisprudence for the same legal problem; in particular, access to the provision of services excluded from the Mandatory Health Plan (POS). This action for protection, in addition to helping to guarantee the attention of users, is an indicator of the efficacy and efficiency of the service, which has set precedents in jurisprudence to review, confirm and repeal administrative and technical actions that limit or violate the rights to health, a dignified life and social security. Keywords: Action for protection; Mental health; Dignified life; Social security; Mental disability.